Genetic changes in the FH gene cause vagal paraganglioma - Snezhkina, Anastasiya V.; Pavlov, Vladislav S.; Kalinin, Dmitry V.; Pudova, Elena A.; Krasnov, George S.; Ayupova, Asiya F.; Kobelyatskaya, Anastasiya A.; Dmitriev, Alexey A.; Atiakshin, Dmitrii A.; Fedorova, Maria S.; Kudryavtseva, Anna V. (Frontiers in Endocrinology, 2024)
Vagal paraganglioma (VPGL) is a rare neuroendocrine tumor that originates from the paraganglion associated with the vagus nerve. Among paragangliomas and pheochromocytomas (PPGLs), VPGLs are considered to have the highest propensity for metastasis. Tumors also present challenges in terms of diagnostics and treatment. VPGL can occur as a hereditary tumor and, like other head and neck paragangliomas, is most frequently associated with mutations in the SDHx genes. However, data regarding the genetics of VPGL are limited. Herein, we report a rare case of a 41-year-old woman with VPGL carrying a germline mutation in the FH gene. Using whole-exome sequencing, a novel variant, FH p.S249R, was identified; no mutations were found in other PPGL susceptibility genesand candidate genes. Loss of heterozygosity analysis revealed the loss of the wild-type allele of the FH gene in the tumor. The pathogenic effect of the p.S249R mutation on FH activity was confirmed by immunohistochemistry for S-(2-succino)cysteine (2SC). Potentially deleterious somatic variants were found in three genes, SLC7A7, ZNF225, and MED23. The latter two encode transcriptional regulators that can impact gene expression deregulation and are involved in tumor development and progression. Moreover, FH-mutated VPGL was characterized by a molecular phenotype different from SDHx-mutated PPGLs. In conclusion, the association of genetic changes in the FH gene with the development of VPGL was demonstrated. The germline mutation FH: p.S249R and somatic deletion of the second allele can lead to biallelic gene damage that promotes tumor initiation. These results expand the clinical and mutation spectra of FH-related disorders and improve our understanding of the molecular genetic mechanisms underlying the pathogenesis of VPGL.